2014
DOI: 10.1093/abbs/gmu015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of erythrocytes in patients with Waldenström macroglobulinemia using atomic force microscopy

Abstract: The pathological changes of erythrocytes are detected at the nanometer scale, which is important for revealing the onset of diseases and diagnosis. The aim of this study is to examine the ultrastructural changes of erythrocytes in Waldenström macroglobulinemia (WM) at a nanometer scale. Blood samples were collected from two healthy volunteers, two WM patients, and three multiple myeloma (MM) patients when they were first diagnosed. The changes of morphology in the erythrocytes were studied at the nanometer lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Recent studies have reported similar changes in the shape of RBCs of the smokers group using the SEM 15 16 17 . Under abnormal physiological conditions, various endogenous or exogenous factors may transform the shape of RBCs, affecting their ability to function.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Recent studies have reported similar changes in the shape of RBCs of the smokers group using the SEM 15 16 17 . Under abnormal physiological conditions, various endogenous or exogenous factors may transform the shape of RBCs, affecting their ability to function.…”
Section: Resultsmentioning
confidence: 55%
“…It may be worthwhile to compare the spectral features of blood components of patients with thalassemia and sickle cell diseases. In these inherited blood disorders, the concentration of metabolites were six or eight folds higher compared to that of the control group 15 16 17 . In other words, the reduced life span of erythrocytes is due to the inherited blood disorders in the case of thalassemia but acquired lifestyle in the case of smoking.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The up and down movement of the cantilever as it walks through the ups and downs of the uneven surface, in a range of a few nanometers, is captured by a laser that is reflected off the head of the cantilever. In comparison to SEM, AFM can provide a 3D image of the surface profile [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, AFM images revealed characteristic circular-shaped holes on the surface of RBCs from systemic lupus erythematosus patients [ 234 ]. RBC morphological parameters (width, length, length to width ratio, valley, peak, valley-to-peak, and surface fluctuation) have been shown to distinguish multiple myeloma (MM) and Waldenström macroglobulinemia from healthy cells and to be useful to follow the effect of disease treatment [ 237 , 238 ]. RBCs from MM patients were extremely deformed and had a macrocytic and canthocytic shape compared with the biconcave healthy shape [ 237 ].…”
Section: Atomic Force Microscopy: Morphometric and Nanomechanical Par...mentioning
confidence: 99%